2001
DOI: 10.3348/kjr.2001.2.4.231
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Inflammatory Pseudotumor Involving the Clivus: CT and MR Findings

Abstract: The authors describe a rare case of inflammatory pseudotumor involving the clivus, where a soft tissue mass lesion, with extension into the prevertebral retropharyngeal space and the cavernous sinuses, was detected by CT and MRI. The mass resembled a malignant tumor or aggressive infectious lesion, and the final diagnosis of inflammatory pseudotumor was a diagnosis of exclusion, decided after histopathological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Clinically, an IPT involving the nasopharynx and skull base causes symptoms, including CN neuropathies, pain and hypopituitarism, as the mass grows and compresses the surrounding tissues [17,19,21,22]. The disease may also present with features suggestive of malignancy, such as disease recurrence, bony erosion/destruction or infiltration of surrounding tissues [19,[23][24][25]. It can be difficult to distinguish between IPT and aggressive malignancy in most cases, because they may have similar clinical or radiographical appearances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, an IPT involving the nasopharynx and skull base causes symptoms, including CN neuropathies, pain and hypopituitarism, as the mass grows and compresses the surrounding tissues [17,19,21,22]. The disease may also present with features suggestive of malignancy, such as disease recurrence, bony erosion/destruction or infiltration of surrounding tissues [19,[23][24][25]. It can be difficult to distinguish between IPT and aggressive malignancy in most cases, because they may have similar clinical or radiographical appearances.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no large series examining the precise effects of systemic steroid therapy on IPT involving the skull base, it has been observed that systemic steroid therapy may help to stabilise or alleviate pain and CN dysfunction [18,21,24]. In a review of literature on orbitsparing IPT of the skull base, Mangiardi and Har-El [20] observed that IPT in this region may be quite responsive to steroid treatment.…”
Section: Nasopharyngeal Inflammatory Pseudotumoursmentioning
confidence: 99%
“…Inflammatory pseudotumors of the head and neck most commonly occur in the orbits, or more rarely in the skull base (1). Inflammatory pseudotumors of the pituitary gland are a very rare non-neoplastic lesion (2).…”
Section: Discussionmentioning
confidence: 99%
“…4 All five patients had homogeneous en-hancement following contrast, with thickening and enhancement of adjacent intracranial dural structures. 1,4,5 The T2 hypointensity is thought to be due to the fibrotic nature of inflammatory pseudotumors, with the relative lack of free water. 4 The hypointensity of the T2 images can help differentiate these tumors from other primary malignant tumors of the skull base such as chordoma, chondrosarcoma, and invasion from nasopharyngeal carcinoma, which are hyperintense on T2.…”
Section: Discussionmentioning
confidence: 99%
“…In the head and neck they have been described in the larynx, trachea, nasopharynx, oropharynx, orbits, meninges, sinuses, salivary glands, thyroid, infratemporal fossa, skull base, and temporal bone. [1][2][3][4][5] We present two patients with very rare inflammatory pseudotumors involving the temporal bone. We present the clinical, histologic, and radiographic features and compare them with previously reported cases.…”
mentioning
confidence: 99%